2015
DOI: 10.1016/j.jamcollsurg.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Using Human Factors and Systems Engineering to Evaluate Readmission after Complex Surgery

Abstract: OBJECTIVE To utilize a human factors and systems engineering approach to understand contributors to surgical readmissions from a patient and provider perspective. BACKGROUND Prior studies on readmission neglect the patient perspective. To address this gap and to better inform intervention design, we evaluated how transitions of care relate to and influence readmission from the patient and clinician perspective using the Systems Engineering Initiative for Patient Safety (SEIPS) model. METHODS Patients readm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
1
20
0
5
Order By: Relevance
“…With minimal access to physician services, it stands to reason that ongoing management of manageable comorbidities would degrade, resulting in rehospitalization. Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours . These hypothesis‐generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With minimal access to physician services, it stands to reason that ongoing management of manageable comorbidities would degrade, resulting in rehospitalization. Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours . These hypothesis‐generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours. 9,21,25,29,31,43 These hypothesis-generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes. If indeed psychosocial and physician access postdischarge are major obstacles for patients and the only viable option for the patient becomes repeated inpatient treatment, then perhaps this would need to be accounted for before hospitals (in the United States) are financially penalized for rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is widely accepted that data‐driven process improvements alone cannot lead to sustained changes in safety culture, as those improvements do not account for biases created by human factors. Multifaceted interventions that bundle standardization of care process with organizational changes that take into account human factors are often necessary to sustain changes in culture safety .…”
Section: Discussionmentioning
confidence: 99%
“…However, we now know that quality communication leads to measurable improved outcomes across a wide variety of health care metrics, including increased patient satisfaction and adherence to medication, enhanced trust in a clinician, 1,2 improved outcomes in a large selection of chronic diseases, [3][4][5][6][7][8] and reduced costs for diagnostic testing and end-of-life care. 9,10 Conversely, studies demonstrate that failures in communication are associated with increased medical errors, [11][12][13] higher readmission rates, 14 decreased outpatient follow-up, 15 and increased malpractice claims. [16][17][18] The Institute of Medicine identified two communication-heavy attributes, patient-centered care…”
Section: Making a Case For Integrated Communication Trainingmentioning
confidence: 99%